Combining design methodologies for the development of a practical and effective approach to erosion control systems - Mokhtar, Nor Aieni; Kassim, Azman; Gofar, Nurly (Universiti Teknologi Malaysia, 2004)
Erosion and slope failure has become common geotechnical problem in tropical region such as Malaysia. This report presents the combining design methodologies for the development of a practical and effective approach to erosion control systems. The study is aimed to apply bio-engineering techniques, using concrete / polymer and incorporating vegetated systems for erosion control and slope stabilization. Three research approaches are adopted namely field monitoring, laboratory modeling, and numerical simulation. Measurements of the rainfall amount, surface runoff, soil loss, pore-water pressure and the evaluation on the effectiveness of the vegetation covers applied on the slope surface are the key subjects to the study. However, the sediment control system was not fully implemented due to the overdue date of completion of the project. Nonetheless, the study would be continued and the funding of the research would be borne by other research grants proposed.